CP-235 Cost–benefit analysis of clinical pharmacist interventions in geriatric wards. (25th February 2017) - Jullien, A; Champarnaud, M; Bouquin, V; Perrier, C; Pierre, E; Pages, A
Abstract : Background: Economic assessment of clinical pharmacist interventions is becoming essential for healthcare providers. Purpose: This study estimated the cost–benefit ratio of clinical pharmacist interventions for 5 months in three geriatric services in a secondary care hospital. Material and methods: To estimate the benefit, we computed for each intervention the cost savings related to drugs and biologic tests added or deleted, and the cost avoidance related to preventable serious adverse drug events (ADEs) avoided by multiplying ADE occurrence probability (Nesbit et al, 2001) by its cost (Rottenkolber et al, 2012). For each intervention a pharmacist and a physician blindly assigned a probability that an ADE would have occurred in the absence of an intervention, according to the Nesbit Scale. When the two experts disagreed, we used the average probability. The inter-rater agreement was assessed by the weighted Cohen's kappa. Cost–benefit ratio was defined as saved or avoided cost divided by investment. Categories of problems and interventions were also analysed. Results: The pharmacy resident performed a total of 1010 interventions and 62% were accepted. The cost savings (related to drugs and biologic tests added or deleted) were €1.04 per intervention. The cost avoidance (related to ADE avoided) was €147.41 per intervention. Investment costs were calculated at €7.74 by intervention. Cohen's kappa was 0.66 (substantial level of agreement according to Landis and Koch scale). The cost–benefit ratio was 19.19:1. The most common type of problem was contraindication and non-compliance to the references, followed by inappropriate methods of administrating the drug, non-necessary medicine and over dosage. The most common type of intervention was substitution and interruption therapy, followed by dosage adjustments. Conclusion: A new model of pharmacy practice that integrates clinical pharmacists into existing clinical practice has the potential to minimise the risks with de-prescription, decrease the costs by substituting a drug that is equally effective or changing the route of administration, thereby improving the outcomes associated with drug therapy, particularly in the elderly. References and/or acknowledgements: Nesbit TW, et al. Implementation and pharmacoeconomic analysis of a clinical staff pharmacist practice model. AM J Health Syst Pharm2001;58:784–90. Rottenkolber D, et al . Costs of adverse drug events in German hospitals—a microcosting study. Value Health 2012;15 :868–85. No conflict of interest